Study on the effect of controlled disproportionation pore-forming and relative vacuum mechanism on the reduction rate of continuous magnesium smelting process - Jing-zhong Xu; Ting-an Zhang; Yan Liu; Zhihe Dou; Yishan Liu; Baiao Feng; Hongxuan Liu (Green Energy & Environment)
Compared with the vacuum continuous magnesium smelting process (RVCMS), its excellent energy saving and emission reduction performance provides a feasible method for green magnesium smelting. In the process of industrialization, the reduction rate of prefabricated pellets affects the yield of metal magnesium and the utilization of reducing slag. In this paper, the reduction mechanism under different carbonate structures is analyzed by controlled disproportionation of prefabricated pellets and micro-nano simulation. The results show that the low temperature decomposition of NH4·HCO3 pore-forming, improve the reduction rate (99.72%) effect is remarkable. Combined with thermodynamics and relative vacuum mechanism, a theoretical model of the relationship between disproportionation pore-forming and reduction rate was established. It was concluded that the energy consumption required to produce per ton of magnesium by adding NH4·HCO3 to the prefabricated pellets was reduced by 0.29–0.34 tce, and the carbon emission was reduced by 1.069–1.263 t. The reduction slag had good compressive strength (Side 101.19 N cm−2, Bottom 466.4 N cm−2). Compared with the 20 MPa reduction slag sample without pore-forming agent, the side compressive strength increased by 51.66%, and the bottom compressive strength increased by 119.10%. The amount of single furnace filler is increased by more than 50%.